Dutch War Letters (1935–1950) to Digital Data - Carlijn Keijzer; Milan van Lange (Journal of Open Humanities Data)
‘First-Hand Accounts of War: War Letters (1935–1950) from NIOD digitised’ created a dataset through a cooperation between archivists, historians, students, and citizen scientists. The original paper records are held by the NIOD. The digitised dataset is available through DANS Data Station Humanities and Social Sciences. The set encompasses (semi-)automated transcriptions and metadata of handwritten personal correspondences from the German Occupation of the Netherlands and the Indonesian War of Independence. Data is available on request for analysis, (re-)use, and further enrichment to GLAM and academic communities. The machine-readable transcriptions facilitate new scalable, systematic, and quantitative historical research as they enhance possibilities of applying computational methods for text mining.